Architecture, materials and languages. From marble to stone and viceversa (Sicily 15th-16th centuries) - Garofalo, Emanuela (Artigrama, 2018)
ResumenEntre la segunda mitad del Cuatrocientos y las primeras décadas del Quinientos, la arquitectura en Sicilia ofrece un caso de coexistencia de dos ‘mundos’ ligados a técnicas y lenguajes relacionados con ámbitos culturales diferentes: Tardogótico y Renacimiento, según las etiquetas de la historiografía tradicional. Este artículo propone una aproximación no convencional que parte de una reflexión sobre los materiales y las prerrogativas profesionales de los representantes de las dos culturas de proyecto como campo de observación para las cambiantes relaciones de fuerza entre las dos. Si en un primer momento la piedra es el campo del Tardogótico y el mármol blanco el del Clasicismo, y las dos realidades conviven, progresivamente —gracias a la naturalización de las dinastías de escultores ‘marmorari’— los ambientes se interrelacionan y se hibridan, hasta la superación de los confines impuestos por los materiales usados y la llegada de los mármoles polícromos locales que preludia la afirmación de un nuevo lenguaje a finales del siglo XVI.AbstractBetween the second half of the 15th century and the early decades of the 16th century architecture in Sicily offers a case of coexistence of two ‘worlds’ related to techniques and languageslinked to different cultural contexts: late Gothic and Renaissance according to the labels oftraditional historiography. This paper proposes an unconventional approach that starts froma reflection on materials and professional prerogatives of the two groups holders of differentproject cultures, as a field of observation for the changing balance of power between them. Ifinitially the stone is the field of the Late Gothic and the white marble that of Classicism andthe two realities coexist, then —also thanks to the naturalization of the dynasties of sculptors‘marmorari’— the two areas intertwine and hybridize, until the completion of the boundariesimposed by the materials used and the advent of local polychrome marble which is a prelude tothe affirmation of a new language at the end of the 16th century.Key wordsMarble, Stone, Sicily, Renaissance.